Application of whole-cell fluorescent in situ hybridization (FISH) of molecular detection of toxic alexandrium species - Cheah, Bi Xuan (Universiti Malaysia Sarawak (UNIMAS), 2011)
Paralytic shellfish poisoning is a type of seafood poisoning due to contamination of a group of neurotoxin, collectively known as saxitoxin, in filter feeding mollusks. Monitoring of PSP producing organism especially from the genus of Alexandrium is very challenging as identification of toxic species is only possible based on plate tabulation. In this study, oligonucleotide probes using whole cell fluorescence in situ hybridization (FISH) to detect toxic A. tamiyavanichii and A. minutum were developed. In silico probe design for the 2 species was carried out using sequences database of Alexandrium species found in Malaysia. Probe specificity was assessed based on GC content, melting temperature, Gibbs free energy change and E value. Potential species-specific probes for A. minutum and A. tamiyavanichii were designated as [L-S-Amin-680- (A. minutum)-A-24] and [L-S-Atam-286-(A. tamiyavanichii)-A-23]. Specific probe for A. tamiyavanichii, TAMIS1 was synthesized and tested against A. tamiyavanichii and all other related species. Probe uniC and uniR were applied as positive and negative control. Our result show high specificity of TAMIS1 to A. tamiyavanichii with no cross-reactivity to four other Alexandrium (A. minutum, A. leei, A. tamarense and A.affine). FISH condition applied in this study with hybridization temperature, 35 °C and formamide 40 % work well with no unspecific binding observed. The probe TAMIS1 should be adopted in national HAB monitoring program in order to increase the efficiency in detection of A. tamiyavanichii.